PENGARUH KUALITAS PRODUK, LIFESTYLE DAN DIGITALISASI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE PADA MARKETPLACE SHOPEE DI JAKARTA - Rahman, Arif; Ariandi, Fajri; Arista, Roynaldi; Utama, Dani Chandra; Warsono, Warsono (JURNAL LENTERA BISNIS, 2025)
The millennial generation in Indonesia today is not only keeping up-to-date with technology, but also with fashion and skincare products. Besides gadgets and fashion, skincare is one of the most sought-after products by the younger generation. This is because it is relatively easy to find and obtain affordable, high-quality skincare products on marketplaces and e-commerce platforms like Shopee. The purpose of this study is to examine and analyze the influence of product quality, lifestyle, and digitalization on purchasing decisions. The research method used was a quantitative approach with accidental sampling, and a sample size of 150 respondents. The results indicate that the variables of product quality, lifestyle, and digitalization have a positive and significant influence on consumer purchasing decisions, both simultaneously and partially.